isolation of Toxoplasma gondii histocysts from Local Chickens , Wild and Domestic Pigeons - Hamza, Hadi M.; Dakhel, Mohamed H. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study conducted to isolate and diagnose Toxoplasma gondii in three species of birds include Gallus gallus domisticus (150 samples), Columba livia domisticus (130 samples) and Columba livia(130 samples) to be the total number 410 samples during the period from October 2010 to May 2011. The samples was collected from different regions of the Al-Diwaniya province. the study aimed as well as to isolate and diagnose Toxoplasma gondii, study infection rates and severity and the role of birds in the transfer toxoplasmosis to human. The results of laboratory tests based on the latex agglutination test (LAT) showed presence of toxoplasmosis infection disease caused by parasitic Toxoplasma gondii with different rates. The results of immunological tests for 150 serum samples from Gallus gallus domisticus showed that 49 samples were positive with rate 32.6%. While the results of examination of 130 serum samples from Columba livia domisticus showed that 32 samples were positive with percentage 24.6%. while the results of examination of 130 samples serum from Columba livia showed that 42 samples were positive with percentage 32.3%. The tissue cysts have been isolated from number of organs (heart, brain, lungs and liver) of the birds studied were positive for the latex agglutination test (LAT) by using dissecting. The results showed that the highest rate of infection was in the liver (34.6%) in the Gallus gallus domisticus and 28% in the Columba livia domisticus and 19% in the Columba livia. As well as the egg cyst was isolated from the intestines of a bird infected during the autopsy. The results of the current study also revealed a major role of domestic birds in transfer of toxoplasmosis infection to humans as one of the common diseases among humans, animals through determination the parasite specific gene in the serum and isolation of the tissue cysts from the organs. The current study is considered the first in Iraq about the Toxoplasma gondii in these birds as well as isolation of tissue cysts from its organs is also the first kind in Iraq.